Predictors of exercise-induced arrhythmias in early stages of treadmill test in hypertensive males - M. Y. Kolesnyk; M. V. Sokolova (Zaporozhye State Medical University, 2014)
M. Y. Kolesnyk, M. V. Sokolova Aim. Early exercise-induced cardiac arrhythmias may have an adverse prognostic value in patients with arterial hypertension. The aim of the study was to estimate the clinical and instrumental features of the cardiovascular system in hypertensive patients with early exercise-induced arrhythmias and to fi nd the predictors of their manifestation. Methods and results. We enrolled 249 hypertensive males who underwent treadmill test. A combination of supraventricular and ventricular extrasystoles was registrated most commonly at the fi rst stage of the test. Patients with exercise-induced arrhythmias were characterized by increased target organs damage severity. Conclusion. Independent predictors of early exercise-induced cardiac arrhythmia are age, left ventricular mass index, low exercise tolerance and blood pressure variability.